Problematika Pendidikan: Analisis Kendala Pembelajaran di Sekolah Dasar Berdasarkan Hasil Belajar Siswa - Chaeroh, Miratu; Nur, Yusmaniar Afifah (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
Education plays a vital role in human life. Every person deserves access to fair and equal educational opportunities. However, numerous challenges persist within the education system. At the elementary school level, one of the common issues is the difficulty students face during the learning process. Throughout teaching and learning activities, various obstacles often arise, which can be identified through the students' academic performance. These learning outcomes serve as measurable indicators to evaluate the effectiveness of educational processes. This study aims to explore the learning barriers in elementary schools as reflected in students' academic achievements. A descriptive method with a qualitative approach was employed in the research. The results highlight specific learning constraints present in elementary schools, as identified through students’ learning outcomes.